2008
DOI: 10.1080/03014460802154777
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche of three-generation families in Taiwan

Abstract: The results showed a significant decrease in the onset age of menstruation over three generations, with a positive effect on age at menarche from mothers to daughters and from grandmothers to granddaughters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 57 publications
4
19
0
2
Order By: Relevance
“…Recent studies reported the mean AAM in Asians to be from 13 to 11.67 years [26, 27]. This is similar to Caucasians, but the secular trend is more pronounced in Asians.…”
Section: Resultsmentioning
confidence: 64%
“…Recent studies reported the mean AAM in Asians to be from 13 to 11.67 years [26, 27]. This is similar to Caucasians, but the secular trend is more pronounced in Asians.…”
Section: Resultsmentioning
confidence: 64%
“…En una investigación realizada por nuestro grupo, con una sub-muestra de adolescentes participantes del presente estudio que incorporó mediciones antropométricas 14 , se demostró en el modelo final ajustando por escolaridad de la madre, que el sobrepeso y la obesidad determina significativamente reducción de la edad de menarquia y que el factor étnico aunque retrasa esta edad no alcanza significación estadística (p = 0,081). Por estos resultados, es posible suponer que el factor genético puede estar regulando esta situación sobre todo en aquellas niñas que no presentan sobrepeso u obesidad encontrándose en ellas edades de menarquia más tardías que influyan en los resultados del grupo indígena 42,43 .…”
Section: Discussionunclassified
“…Algunos estudios indican que la edad de menarquia en Chile estaría estacionaria desde la década de los 1970-79 46 , sin embargo, otra investigación realizada en la Región de La Araucanía muestra una tendencia secular hacia una menarquia más temprana en las últimas décadas sin diferenciación étnica 43 . Lo anterior, en conjunto con los resultados de esta investigación, deja abierta la posibilidad de que la edad de menarquia aún no se estabilice, sobre todo en poblaciones que están todavía en proceso de mejoramiento de sus condiciones de vida.…”
Section: Discussionunclassified
“…The current literature, indeed, convincingly demonstrates that a woman's reproductive life span to a large extent is genetically predetermined. 9, 13 Hefler et al, 23 for instance, show a statistically significant association between various polymorphisms and age at menopause. In contrast, data by Otero et al 24 lack correlations between age at menarche and age at menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies suggest significant concordance of age at menarche Twin studies suggest significant concordance of age at menarche between monozygotic and dizygotic twins. 12 Generational studies, in turn, have suggested that ethnicity and mother's and grandmothers ages at menarche are highly predictive parameters for menarchal age (13).…”
Section: Introductionmentioning
confidence: 99%